FAKTOR-FAKTOR YANG MEMPENGARUHI PARTISIPASI MASYARAKAT PADA KEBUN BIBIT RAKYAT (Studi Kasus Pengadaan Bibit Karet Untuk Petani di Kota Banjarbaru) - Ditha Tri Hapsari; Suprijanto Suprijanto; Marijati Sangen; Susilawati Susilawati (Universitas Lambung Mangkurat, 2012)
The research was conducted in South Kalimantan Banjarbaru City is in the Mount Sustainable Farmers Group in the Village District Banjarbaru Paikat blunt, and Farmers Group Forward Together Batu Ampar Village District Sub Cempaka Cempaka Banjarbaru. In particular, this study aims to: 1). To analyze the level of public participation in government programs on KBR, 2). To analyze the factors that influence people's participation to the presence of KBR. Independent variables in this study were community participation, while dependent variables are age, length of residence, education, occupation, gender, and income. Based on the analysis of data it can be concluded that the level of public participation against KBR, according to the analysis of the data obtained are significantly lower, in which there were nine respondents who have a high participation rate and the 25 respondents who have a low value of participation. So that the average level of community participation amount to 62.37% of 34 respondents. From the analysis using the Kruskal Wallis test is processed using the note, the six factors that influence people's participation there is the People's Garden Seeds, there are two factors that significantly affect people's participation is the sex of the χ2 count (15 007)> χ2 table 1: 0.05 (3841) and work with the χ2 count (7341)> χ2 table 1: 0.05 (3841).